Metode Pengumpulan Data tentang Data Setiap Mahasiswa STIKes Santa Elisabeth Medan Prodi Manajemen Informasi Kesehatan - Leoni Putri Caantika Hulu; Nduru, Mitra Amelia; Laia, Tri Karolina; Daniel Emanuelta Ginting (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Assessment research data was taken in July from 30 students of the same major. Data was collected using a questionnaire. The data was filled online through google from. This study discusses data on age, height, and weight of each student of Stikes Santa Elisabeth Medan, health information management study program for each generation. The research results can be seen in the following table. The type of research used is qualitative research. The collection technique is through a questionnaire that focuses on data regarding age, height, weight, every student of the Health Information Management study program at each level. The sample in this study was 30 students of the same department, namely the MIK (health information management) department. From the results of the questionnaire that we have collected above, it is found that the highest average age, height and weight are obtained in MIK students at level 1. The research method we use is a skinative data collection method using a questionnaire. Where we gave several questions including name, level, age, height, weight. 30 respondents who have answered several questions from us. The use of questionnaires as a method of collecting data on the age, height, and weight of students provides adequate and reliable results for further analysis. This method supports data-driven decision making in the context of academic and health research.